Cenozoic Ampullinidae and Naticidae (Mollusca, Gastropoda) from Patagonia, Argentina - Griffin, Miguel (2013)
A revision of the Cenozoic Ampullinidae and Naticidae from a wide range of localities and stratigraphic units in Patagonia revealed the occurrence there of thirteen species referable to these families. Ampullinid species described are Tejonia? tapia (Feruglio, 1935); Tejonia arroyoensis n. sp. and Pseudamaura dubia (Petersen, 1946). Naticids are represented by the following valid species: ‘‘Natica’’ entreriana Borchert, 1901; Euspira patagonica (Philippi, 1845); Notocochlis borrelloi (Brunet, 1995); Bulbus subtenuis (Ihering, 1897); Polinices santacruzensis Ihering, 1907; Polinices puntarenasensis Ihering, 1907; ‘‘Polinices’’ ortmanni Ihering, 1907 (nomen dubium); Polinices mina n. sp.; Glossaulax secundum (Rochebrune and Mabille, 1885); and Darwinices claudiae n. gen. n. sp.